Integration of HIV prevention and sexual and reproductive health in the era of anti-retroviral-based prevention: findings from assessments in Kenya, Malawi and Zimbabwe [version 2; peer review: 1 approved, 3 approved with reservations] - Fannie Kachale; Fatima Mhuriro; Imelda Mahaka; Joseph Murungu; Mary Mugambi; Getrude Ncube; Barbra Ncube; Rose Nyirenda; Albert Ndwiga; Anna Carter; Violet Otindo; Janet Fleischman; et al. (Gates Open Research, 2022)
Background: Though substantial progress has helped curb the HIV epidemic, high rates of new HIV infections persist among adolescent girls and young women (AGYW) in sub-Saharan Africa, reflecting critical gaps in reaching them with integrated HIV prevention and sexual and reproductive health (SRH) services. The scale-up of oral pre-exposure prophylaxis (PrEP) and multiple novel HIV prevention products on the horizon offer countries a unique opportunity to expand innovative approaches to deliver comprehensive, integrated HIV prevention/SRH services. Methods: This article comparatively analyzes findings from rapid assessments in Kenya, Malawi and Zimbabwe across key themes to highlight cross-country trends and contextual realities around HIV prevention/SRH integration, with a focus on oral PrEP and contraception. In Kenya and Zimbabwe, assessments were completed by Ministries of Health (MOH) and the HIV Prevention Market Manager and include 20 health facility assessments, 73 key informant interviews (KIIs) and six community dialogues. In Malawi, the assessment was completed by the MOH and Georgetown University Center for Innovation in Global Health and includes 70 KIIs and a review of national policies and program implementation in Blantyre. Findings were contextualized through a review of literature and policies in each country. Results: Across countries, the policy environment is conducive to HIV prevention/SRH integration, though operationalization presents ongoing challenges, with most policies preceding and not accounting for oral PrEP rollout. National coordination mechanisms, youth-friendly health services and prevention of mother-to-child transmission programs are promising practices, while siloed and resource-constrained health systems, limited provider capacity, underfunded demand generation and structural factors exacerbate barriers to achieving integration. Conclusions: As new HIV prevention products are introduced, demand for integrated HIV prevention/SRH services is likely to grow. Investing in HIV prevention/SRH integration can help to ensure a sustainable response to the HIV epidemic, streamline service delivery and improve the health outcomes and lives of AGYW.